The go-kart English - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford reading press UK, 2012)
In "The Go-Kart," the children build a go-kart using various materials they find. Dad helps them put it together. Everyone is excited to try it out. When it$1 (Bs ready, the children take turns riding it. But when it$1 (Bs Mum$1 (Bs turn, the go-kart goes too fast and crashes into a bush! Everyone laughs, and Mum is okay. It's a fun and lighthearted story about teamwork, creativity, and a little bit of adventure.s
The Level 2 Biff, Chip and Kipper Stories provide humorous story lines to engage and motivate children. The popular characters and familiar settings are brought to life by Roderick Hunt and Alex Brychta. The stories are unchanged from the previous edition but the cover notes have been updated to support adults in sharing the story with the child.
H3
Keywords: Supplementary reading material